2016
DOI: 10.3390/jcdd3030025
|View full text |Cite
|
Sign up to set email alerts
|

Ciona as a Simple Chordate Model for Heart Development and Regeneration

Abstract: Cardiac cell specification and the genetic determinants that govern this process are highly conserved among Chordates. Recent studies have established the importance of evolutionarily-conserved mechanisms in the study of congenital heart defects and disease, as well as cardiac regeneration. As a basal Chordate, the Ciona model system presents a simple scaffold that recapitulates the basic blueprint of cardiac development in Chordates. Here we will focus on the development and cellular structure of the heart of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 138 publications
0
42
0
Order By: Relevance
“…Cardiopharyngeal ontogenetic motif in Ciona . In ascidian embryos, cell fates are first restricted to a few progenitors, which are secondarily amplified (From Anderson and Christiaen)…”
Section: Cardiac Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiopharyngeal ontogenetic motif in Ciona . In ascidian embryos, cell fates are first restricted to a few progenitors, which are secondarily amplified (From Anderson and Christiaen)…”
Section: Cardiac Precursorsmentioning
confidence: 99%
“…These will be guided by chamber‐specific gene interactions involving Tbx1, Tbx2, Nkx2.5, and ANF or will embrace a ventricular fate in the absence of retinoic acid signaling, which also belongs to the cardiac tool kit. Gene regulatory networks determining the interactions in the various precursors have been summarized by Herrmann et al and Anderson and Christiaen . See also Figure .…”
Section: The First Heart Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although the beating Ciona heart is demonstrably simpler than its vertebrate counterpart, the single-compartment U-shaped adult heart is encased in a pericardial squamous epithelium, it contains two pacemakers at either ends of the tube, an epithelial row of undifferentiated cells, the contractile wall is composed of myoepithelial cells, and endothelial cells are missing altogether (Anderson and Christiaen, 2016;Davidson, 2007) . In 2 to 3 day old post-metamorphic juveniles, the heart has not yet acquired its characteristic shape, but it already beats peristaltically, and double labeling with a B7.5-lineage-specific Mesp>nls::lacZ reporter and the cardiac-specific myosin heavy chain 2 ( Mhc2 ) marker showed that a β-galactosidase+; Mhc2 -pericardium already encases Mhc2 + cardiomyocytes (Stolfi et al, 2010;Wang et al 2013).…”
mentioning
confidence: 99%
“…At the onset of neurulation, each founder cell divides asymmetrically to produce a larger anterior tail muscle cell and a smaller heart progenitor cell (TVC). FGF activates mitogen activated protein kinase signaling (MAPK) in the TVCs, initiating a well-characterized transcriptional program that induces heart progenitor fate (Evans-Anderson and Christiaen 2016; Cota et al 2017). During heart progenitor induction, founder cells are exposed uniformly to FGF (Cooley et al 2011).…”
Section: Fusion Proteins For Visualization Of Cellular Processes In Amentioning
confidence: 99%